Long-term effects of stem cell transplantation in heart failure - Haddad, F. (Zdravniški vestnik, 2012)
Background: We investigated long-term effects of intracoronary transplantationof CD34+ cells in patients with dilated cardiomyopathy (DCM). Methods: Of 110 DCM patients, 55 were randomized to CD34+ cell transplantation(SC) group, and 55 patients received no cell therapy (controls). In the SC group, peripheral CD34+cells were mobilized by G-CSF andcollected via apheresis. Patients underwent myocardial scintigraphy and CD34+ cells were injected in the artery supplying the segments with reduced viability. Patients were followed for 5 years. Results: At baseline, the 2 groups did not differ in age, gender, left ventricular ejection fraction (LVEF), or NT-proBNP levels. At 5 years, stem cell therapy was associated withan increase in LVEF (from 24.3 Ž 6.5 % to 30.0 Ž 5.1 %; P = 0.02), an increase in 6-minute walk distance (from 344 Ž 90 m to 477 Ž 130 m; P < 0.001), and a decrease in NT-proBNP (from 2322 Ž 1234 pg/mL to 1011 Ž 893 pg/mL; P < 0.01). During followup, 27 (25 %) patients died and 9 (8 %) underwent heart transplantation. Of the 27 deaths, 13 were attributed to pump failure, and 14 to sudden cardiac death. Total mortality was lower in SC group(8/55 14 %) than in controls (19/55 35 %) (P = 0.01). The same was true of pump failure (3/55 5 % vs. 10/55 18 %, P = 0.03), but not of sudden cardiac death (5/55 9 % vs. 9/55 16 %, P = 0.39). SC therapy was anindependent predictor of outcome on multivariable analysis (P = 0.04). Conclusions: Intracoronary stem cell transplantation may be associated with improved ventricular remodeling, exercise tolerance, and longterm survival in patients with DCM.
Keywords: dilated cardiomyopathy; dilativna kardiomiopatija; heart failure; matične celice; srčno popuščanje; stem cells